Norman Mailer revisited - Merrill, Robert, 1944- (New York : Maxwell Macmillan International, 1992)
Assessment of Mailer's entire fiction and nonfiction output, placing him among one of the most influential in both genres since World War II.
Includes bibliographical references (p. 231-238) and index.
Young Adult.
Young Adult
Keywords: Mailer, Norman -- Criticism and interpretation; Mailer, Norman